Explaining Left-Right Party Congruence across European Party Systems: A Test of Micro-, Meso- and Macro-Level Models. - Belchior, Ana Maria (2013)
Empirical studies on representation have been based mainly on the descriptive analysis of levels of political or ideological congruence between MPs and voters. Very few studies focus on explaining congruence, and those that have done so do not explore all the explanatory dimensions. This article contributes to filling this gap by testing whether three theoretical models can explain left–right congruence among European parties. These models explore causality at the micro or individual level (the characteristics of voters and MPs), the meso level (party characteristics), and the macro or system level (party system and institutional characteristics). Based on data from the PIREDEU project, the study examines the party systems of the 27 countries of the European Union with reference to the 2009 European Parliament elections. The findings reveal that MP–voter congruence is best explained at the party level and by key MP candidate characteristics.